An Update of Long-Noncoding RNAs in Acute Kidney Injury - Yang, Lina; Wang, Bo; Ma, Liang; Fu, Ping (Frontiers in Physiology, 2022)
Acute kidney injury (AKI) is a global public health concern with high morbidity, mortality, and medical costs. Despite advances in medicine, effective therapeutic regimens for AKI remain limited. Long non-coding RNAs (lncRNAs) are a subtype of non-coding RNAs, which longer than 200 nucleotides and perform extremely diverse functions in biological processes. Recently, lncRNAs have emerged as promising biomarkers and key mediators to AKI. Meanwhile, existing research reveals that the aberrant expression of lncRNAs has been linked to major pathological processes in AKI, including the inflammatory response, cell proliferation, and apoptosis, via forming the lncRNA/microRNA/target gene regulatory axis. Following a comprehensive and systematic search of the available literature, 87 relevant papers spanning the years 2005 to 2021 were identified. This review aims to provide and update an overview of lncRNAs in AKI, and further shed light on their potential utility as AKI biomarkers and therapeutic targets.